Effects of neglected anterior cruciate ligament tears on medial and lateral meniscus - M. P., Jeevan; John, John T. (International Journal of Research in Orthopaedics, 2020)
Background: The effects of neglected anterior cruciate ligament (ACL) tears and its impact on the medial and lateral meniscus was evaluated in this study over a one-year time period patients were grouped on the basis of their injury to treatment time. The study emphasized the importance of early treatment of ACL injury to prevent damage to the meniscal tissue and secondary osteoarthritis. Methods: Retrospective cohort study undertaken in the Department of Orthopaedics at Lourdes Hospital, Ernakulam, Kerala. Over a time period of one year starting from 2010 February. A total of 101 patients was analysed in whom Meniscal injury associated with ACL tear was noted. The patients were grouped into three based on the time from initial injury to the time of reconstruction. Acute injury (treated within 4 months of injury) sub-acute injury (treated between 4 and 8 months after injury) chronic injury (treated between 8 and 12 months after injury). The trend of meniscal injury based upon the injury to treatment time was analysed using appropriate statistical methods. Results: Immediately following ACL injury lateral meniscal injuries were more common and was found in the acute phase. Lateral meniscus tears decreased as patients passed through the acute phase into the sub-acute phase, whereas medial meniscal tears began to increase and predominated in the chronic phase. Medial meniscal injuries were common in chronic ACL tears which were often complex tears not amenable to repair. Conclusions: This study was able to demonstrate that the incidence of meniscal injury increased over time in ACL damaged knees.